Sosialisasi Mencetak Generasi Anti Bullying di Sekolah Dasar Negeri 004 Desa Dusun Tua Pelang Kecamatan Kelayang Kabupaten Indragiri Hulu - Dewi Hartika; Gustika, Gita Sari; Yaspita, Hasanah (Yayasan Sagita Akademia Maju, 2025)
Bullying is an act of violence that is intentionally carried out by one or a group of people against others repeatedly either by physical violence, verbal violence or through social media. The school environment is one of the highest locations for bullying. Bullying prevention socialization is needed for students in the school environment. The purpose of this activity is to educate students about bullying and prevent bullying in the school environment. The method used was lectures, interactive discussions and quizzes with prizes. The results of this activity are increasing student awareness to be able to prevent bullying behavior, instill a sense of concern for victims of bullying, report bullying perpetrators and instill sensitivity to the social environment.